Phenomenology and Social Reality
XII, 308 p.
Keywords: Alfred Schutz was born in Vienna on April 13, 1899, and died in New York City on May 20, 1959. The year 1969, then, marks the seventieth anniversary of his birth and the tenth year of his death. The essays which follow are offered not only as a tribute to an irreplaceable friend, colleague, and teacher, but as evidence of the contributors' conviction of the eminence of his work. No special pleading is needed here to support that claim, for it is widely acknowledged that his ideas have had a significant impact on present-day philosophy and phenomenology of the social sciences. In place of either argument or evaluation, I choose to restrict myself to some bi~ graphical information and a fragmentary memoir. * The only child of Johanna and Otto Schutz (an executive in a private bank in Vienna), Alfred attended the Esterhazy Gymnasium in Vienna, an academic high school whose curriculum included eight years of Latin and Greek. He graduated at seventeen - in time to spend one year of service in the Austrian army in the First World War. For bravery at the front on the battlefield in Italy, he was decorated by his country. After the war ended, he entered the University of Vienna, completing a four year curriculum in only two and one half years and receiving his doctorate in Law.